2021
DOI: 10.3390/cells10071701
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation in the Charged Linker Modulates Interactions and Secretion of Hsp90β

Abstract: Hsp90β is a major chaperone involved in numerous cellular processes. Hundreds of client proteins depend on Hsp90β for proper folding and/or activity. Regulation of Hsp90β is critical to coordinate its tasks and is mediated by several post-translational modifications. Here, we focus on two phosphorylation sites located in the charged linker region of human Hsp90β, Ser226 and Ser255, which have been frequently reported but whose function remains unclear. Targeted measurements by mass spectrometry indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…We identified two sites in HSP90 (Ser226, Ser255), which were significantly diminished by PP5 treatment. Both of these CK2 sites are within the charged linker segment connecting the N and middle domains of HSP90 and have been implicated in the regulation of HSP90β secretion 39 . We identified multiple sites in BRAF V600E whose phosphorylation was significantly (p < 0.05) decreased by PP5 treatment (Fig.…”
Section: Pp5 Phosphatase Targetsmentioning
confidence: 99%
“…We identified two sites in HSP90 (Ser226, Ser255), which were significantly diminished by PP5 treatment. Both of these CK2 sites are within the charged linker segment connecting the N and middle domains of HSP90 and have been implicated in the regulation of HSP90β secretion 39 . We identified multiple sites in BRAF V600E whose phosphorylation was significantly (p < 0.05) decreased by PP5 treatment (Fig.…”
Section: Pp5 Phosphatase Targetsmentioning
confidence: 99%
“…We identified two sites in HSP90 (Ser226, Ser255) which were significantly diminished by PP5 treatment. Both of these CK2 sites are within the charged linker segment connecting the N and middle domains of HSP90, and have been implicated in regulation of HSP90β secretion 37 . We identified 12 sites in BRAF V600E whose phosphorylation was significantly (p < 0.05) decreased by PP5 treatment (see SUPPLEMENTARY MATERIAL ).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, overexpression of the constitutively activated JAK2 mutant (harboring the V617F variant) in HEK293 and HAP1 STIP1 KO cells were found to increase wild-type STIP1 protein levels in culture medium, which were conversely reduced when the STIP1 double mutant was used ( Figure 6 c,d). Interestingly, a previous study reported that the phosphorylation status of JAK2 can regulate HSP90 secretion [ 51 ]. Higher amount of HSP90 β is identified in conditioned medium when two phosphorylated sites, S225 and S255, on HSP90 β are mutated to alanine [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a previous study reported that the phosphorylation status of JAK2 can regulate HSP90 secretion [ 51 ]. Higher amount of HSP90 β is identified in conditioned medium when two phosphorylated sites, S225 and S255, on HSP90 β are mutated to alanine [ 51 ]. Our findings raise the interesting possibility that JAK2 inhibition may be a viable strategy to inhibit STIP1 release in the extracellular space.…”
Section: Discussionmentioning
confidence: 99%